ADMINISTRATIVE SETTLEMENT OF CUSTOMS OFFENSES: ON THE EXAMPLE OF ART. 485 UCC - Кунєв, Юрій Дем`янович; Лівінська, Карина Костянтинівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose of the article is to formulate proposals on the possibility of achieving the goal of administrative penalty under art. 23 of the Code of Ukraine on Administrative Offenses on the basis of the problems analysis of the customs legislation according to art. 485 of the Customs code of Ukraine. Research methods: system analysis and synthesis, comparative legal and doctrinal cognition of customs legislation; methods of comparison and comparing the provisions of international and national customs legislation, as well as the method of generalization and modeling of new theoretical knowledge. Results: problems of further development of administrative settlement of customs offenses are defined and certain ways of their decision are offered. To systematically solving of all the identified problems, it is necessary to link security to regulations and the division of misdemeanors by specific customs procedures for the movement of goods, which, in turn, can also be grouped by general procedures: import, export and transit. The model of construction of the norm, which determines the responsibility under the Customs Code of Ukraine, must contain a clear definition of all components of the legal norm, where legal means combine the regulatory norm and the composition of the offense for violation of this regulatory norm. That is, it is necessary to provide a specific set of actions, for the violation of which there is a specific, individually determined legal liability. Discussion: argues that all existing articles of customs legislation should be checked for compliance with the constitutional principles of responsibility and standards of responsibility in the customs sphere, set out in international treaties and agreements ratified by Ukraine.